Effects of active ingredients from traditional Chinese medicines on glycogen molecular structure in diabetic mice. (March 2019) - Li, Cheng; Gan, Hua; Tan, Xinle; Hu, Zhenxia; Deng, Bin; Sullivan, Mitchell A.; Gilbert, Robert G.
Graphical abstract: Highlights: Liver glycogen α particles from diabetic mice is molecularly fragile. This fragility may contribute to diabetic hypoglycemia. Effects of 4 traditional Chinese medicines with proven efficacy were tested. TCM active ingredients were checked for effects on this fragility. Three drugs tested both reduced blood glucose level and repaired fragility. Abstract: Glycogen, a complex branched glucose polymer, is a blood-sugar reservoir; it comprises β particles (∼20 nm in size), which can link together into larger (>40 nm) α particles. In type 2 diabetic mice, liver-glycogen α particles are fragile, degrading into β particles in the presence of a hydrogen-bond disruptor (dimethyl sulfoxide); this is detected by analyzing the molecular structure (the weight distribution as a function of molecular size) with size-exclusion chromatography (a type of gel-permeation chromatography, GPC). The β particles quickly degrade enzymatically to glucose, with implications for diabetic hyperglycemia. We examine if this fragility is altered by using active ingredients from traditional Chinese medicines (TCMs) with proven efficacy for managing some diabetes symptoms. Glycogen molecular structural differences between astragalus polysaccharide (APS), berberine (BBR), panax notoginseng saponins (PNS) and pueraria flavonoid (PF)-treated and untreated diabetic mouse glycogen were studied. With APS, BBR and PF, the glycogen showed no significant fragility: effective medication can strengthen impaired glycogen fragility in diabetes. This may provide a new way to check the efficacy of individual components of TCM and to explore drug targets for diabetes.